Mannerheim the Finnish years - Screen, John E. O. 1939-2009 (Hurst & Company, 2014)
PREFACE AND ACKNOWLEDGEMENTS -- I. THE WHITE GENERAL 1 -- Finland in 1917- Mannerheim's career in Russia - From 'exile' to -- command - From planning to action - War begins - Organizing -- an army- Mannerheim's strategy and German intervention- -- Towards victory - Triumph - Resignation -- II. REGENT 43 -- In Sweden - From unofficial diplomat to regent - Military and -- foreign policy problems - Elections and a newgovernment - -- The constitution - Intervention in Russia? - Stylish regent -- but rejected presidential candidate - Departure abroad -- III. CIVILIAN 74 -- Advocate of intervention - Private life - Travel - Humanitarian -- work - Passed overforpublic service -- IV. CHAIRMAN OF THE DEFENCE COUNCIL 104 -- Lapua and Mintsala - Work in the Defence Council- Seventieth -- birthday celebrations - The language problem - Foreign relations - -- Resignation? - Negotiations with the Soviet Union continued - -- From resignation to commander-in-chief -- V. THE WINTER WAR 137 -- At war- War orpeace?- The exercise of supreme command -- VI. THE'ARMISTICE' 160 -- Peacetime commander-in-chief- In the 'War Cabinet' - Finland -- and German plans- Towards war -- VII. THE CONTINUATION WAR 177 -- Successful Finnish offensives but no German victory - Wartime -- GHQ - Health - Attempts to leave the war- Near disaster -- VIII. PRESIDENT 206 -- Presidentforpeace - Under the Control Commission - Power slips -- away - Health deteriorates - The war responsibility case - -- Resignation -- IX. TESTAMENT 240 -- Retirement - The Memoirs - Death - The man - The legacy -- BIBLIOGRAPHY 268 -- INDEX 279.